COMPARATIVE STUDY OF ENVIRONMENTAL AWARENESS OF SECONDARY SCHOOL STUDENTS - Kumar, Nitin; Singh, Rajkumari (ShodhKosh: Journal of Visual and Performing Arts, 2023)
It is very important to increase the environmental awareness of secondary school students. For this, there is a need to improve the education system, curriculum, teacher training, and school activities. Along with this, the cooperation of society and family is also important. Environmental awareness of students not only leads to their personal development, but also benefits the society and the country. Therefore, we should work together in this direction and ensure a safe and healthy environment for the coming generations. Findings from the research - No significant difference was found in the environmental awareness of students of secondary schools, no significant difference was found in the environmental awareness of urban and rural students of secondary schools.